Barriers in the Foreign Workers in Industry: Investigation during Training - Wahab, Nurhana Abd; Mahmood, Nik Hasnaa Nik; Minghat, Asnul Dahar (Universitas Pendidikan Indonesia (UPI), 2023)
The purpose of this study was to review barriers in the foreign workers in Industry. We took data for the industry in Malaysia. This study was conducted based on only 55 workers from the Nadayu site. It is recommended that the study be carried out in a larger sample and involvement of the Construction Industry Development Board (CIDB) and the registered CIDB contractor. This study focus on the language barrier, safety knowledge, and background of workers, and these factors contribute to the effectiveness of training. It is proposed to have an in-depth study on the syllabus, methodology of training, motivation, and commitment of the company to improve CIDB training.